Galectin-3 expression is ubiquitous in tumors of the sellar region, nervous system, and mimics - An immunohistochemical and RT-PCR study - Rodriguez, FJ; Scheithauer, BW; Roncaroli, F; Silva, AI; Kovacs, K; Brat, DJ; Jin, L (Lippincott Williams Wilkins, 2008)
Galectin-3 expression has been reported in spindle cell oncocytoma, certain pituitary adenoma subtypes, astrocytomas, oligodendrogliomas, and meningiomas. We evaluated galectin-3 protein expression by immunohistochemistry in 201 cases of a variety of nervous system and sellar tumors, as well as mRNA expression by reverse transcription-polymerase chain reaction in formalin-fixed paraffin-embedded tissue in a subset (20 cases). Immunohistochemical results were evaluated in a semiquantitative fashion on a 4-tiered scale (0 to 3). Strong (3+) immunoreactivity was seen in most of the cases (61%), followed by 2+(22%), and 1+(13%) staining. Only 4% of the lesions studied were immunonegative. Galectin-3 mRNA was present in 15 of the 18 cases (83%) in which reverse transcription-polymerase chain reaction was successful. Significant differences in protein expression were noted in the following 2 settings: specific meningioma subtypes (P=0.004, Fisher exact test) wherein clear cell meningioma demonstrated weak protein expression when compared with other meningioma variants. No significant difference was noted with respect to World Health Organization grade. Galectin-3 was also strongly expressed in benign nerve sheath tumors but only moderately expressed in malignant peripheral nerve sheath tumors (P=0.0009, Fisher exact test). Although galectin-3 positivity is a key feature of the immunophenotype of spindle cell oncocytoma, its consistent expression in other morphologically similar tumors (meningioma, pituicytoma, nerve sheath tumors, granular cell tumor, metastases) makes it of little use in the differential diagnosis of sellar region tumors, a setting in which it should be discouraged. Diagnostic uses of this marker may be limited to specific settings, including some meningioma subtypes and nerve sheath tumors.
Keywords: Neoplasias Cerebrais; Galectina 3; Neoplasias da Bainha Neural; Sela Túrcica